2021
DOI: 10.1101/2021.01.18.427167
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of Flourishing Levels of Individuals by Using Resting State fNIRS with Different Functional Connectivity Measures

Abstract: Flourishing is an important criterion to assess wellbeing, however, controversies remain, particularly around assessing it with self-report measures. Due to this reason, to be able to understand the underlying neural mechanisms of well-being, researchers often utilize neuroimaging techniques. However, rather than individual answers, previous neuroimaging studies using statistical approaches provided an answer in average sense. To overcome these problems, we applied machine learning techniques to discriminate 4… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 106 publications
0
2
0
Order By: Relevance
“…In this study, functional connectivity features were extracted for the classification tasks because functional connectivity can reflect information propagation. The temporal correlation of regional hemodynamics was estimated by Pearson's correlation which was commonly used to quantify functional connectivity between different brain regions in fNIRS-based studies [26], [27], [28], [29]. The Pearson correlation coefficient is used to measure the degree of linear correlation between two numerical variables.…”
Section: E Feature Extractionmentioning
confidence: 99%
“…In this study, functional connectivity features were extracted for the classification tasks because functional connectivity can reflect information propagation. The temporal correlation of regional hemodynamics was estimated by Pearson's correlation which was commonly used to quantify functional connectivity between different brain regions in fNIRS-based studies [26], [27], [28], [29]. The Pearson correlation coefficient is used to measure the degree of linear correlation between two numerical variables.…”
Section: E Feature Extractionmentioning
confidence: 99%
“…Nevertheless, Kwong and Hayes (2017) have studied flourishing with its three aspects-capability to remain in control when challenged, interest in learning new things and ability to follow through with plans. Research suggests that flourishing is not only an important criterion for assessing well-being (Eken, 2021), but also it serves as a marker for behavioural and social well-being (Lippman et al, 2011;Moore and Lippman, 2006). Recently Whitaker et al (2021) have observed that greater childhood family connection is associated with greater flourishing in US adults across levels of childhood adversity.…”
mentioning
confidence: 99%